Penambahan Biaya Tol oleh Sopir terhadap Penumpang Perspektif Fatwa MUI No. 112/DSN-MUI/IX/2017 Tentang Akad Ijarah: Studi Kasus Perusahaan Travel Trayek Medan-Panyabungan - Nst, Mhd Ilham; Zahara, Fatimah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to examine the conformity of the practice of toll fee additions by drivers to passengers of the Medan–Panyabungan travel route with the provisions of Fatwa DSN-MUI No. 112/DSN-MUI/IX/2017 concerning the ijarah contract. This research employs an empirical approach through data collection techniques including observation, interviews, and documentation. The data analysis technique used refers to the Miles and Huberman model, which consists of data condensation, data display, and conclusion drawing and verification. The findings reveal that the addition of toll fees can be justified according to Islamic law (sharīʿah) if it is communicated beforehand and mutually agreed upon. However, there are practices where toll fees are added unilaterally without prior notice, which potentially leads to gharar (uncertainty) in the contract. Therefore, it is necessary to establish a clear standard operating procedure (SOP) and ensure transparent communication from the outset so that the implementation of the ijarah contract in transportation services complies with sharīʿah principles and avoids future disputes.